Tillage Intensity in a Long-Term Wheat-Sorghum-Fallow Rotation - Lucas A. Haag; Amanda Burnett; Dewayne Bond; Jeffrey Slattery; Alan Schlegel (Kansas Agricultural Experiment Station Research Reports, 2023)
This study was initiated in 1991 at the Kansas State University Southwest Research-Extension Center near Tribune, KS. The purpose of the study was to identify the effects of tillage intensity on precipitation capture, soil water storage, and grain yield in a wheat-sorghum-fallow rotation. Grain yields of wheat and grain sorghum increased with decreased tillage intensity in a wheat-sorghumfallow (WSF) rotation. In 2022, available soil water at sorghum planting was greater for no-tillage (NT) than reduced tillage (RT), which was greater than conventional tillage (CT). For wheat there was a similar pattern as sorghum, with available soil water at wheat planting being in the order of NT>RT>CT. Averaged across the most recent 22 years of the study, available soil water at wheat planting was 0.60 inch greater for NT than RT and approximately 1.7 inches greater than CT. Average available soil water at sorghum planting was greater in the order RT=NT>CT averaging 7.9 inches for RT and NT and 5.9 inches for CT. Averaged across the past 22 years, NT wheat yields were 6 bu/a greater than RT and 10 bu/a greater than CT. Averaged across the past 22 years, sorghum yields with long-term NT have been 57% greater than with RT (82 vs. 52 bu/a).
Keywords: tillage intensity; long-term rotation; wheat; grain sorghum; fallow